Substance use disorders among African, Caribbean and Black (ACB) people in Canada: a scoping review protocol - LaRon E Nelson; Joseph D Nguemo; Ngozi Iroanyah; Winston Husbands; Geoffrey Maina; Irene Njoroge; Maureen Owino; Desmond Miller; Josephine Wong (BMJ Open)
Introduction Previous research demonstrated that substance use continues to be one of the most complex and prevalent problems among African, Caribbean and Black (ACB) people. A number of studies were conducted to characterise substance use patterns in this population. To our knowledge, this is the first known review in Canada characterising substance use disorders on ACB people.This scoping review seeks to answer the following research questions: What characterises substance use disorders among ACB people in Canada? What are the different types and prevalence of substance use among ACB people in Canada? Do ACB people in Canada use more than one substance? What factors are associated with substance use among ACB people in Canada? What are the health and social impacts of substance use in ACB people in Canada?Methods and analyses This study will use the methodological framework for scoping reviews developed by Arksey and O’Malley. We will search electronic bibliographic databases including Ovid MEDLINE, PsycINFO and CINAHL. We will limit our search to English articles published between 2000and2019. In addition, we will conduct a grey literature search. Two investigators will independently screen citations and full-text articles. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for scoping reviews guidelines. We will provide a descriptive summary of the studies and summarise the findings with respect to the outcomes and report any gaps that might require further investigation.Ethics and dissemination Our proposed study does not involve human participants; therefore, research ethics approval is not required. This study will provide evidence that will inform the development of strategies for appropriate interventions, as well as policy and further research. The results will be disseminated through publications in open access peer-reviewed journals, presentations at scientific meetings and to the lay public.